Sustainability Science An Introduction - Heinrichs, Harald; Martens, Pim; Michelsen, Gerd; Wiek, Arnim (Springer Netherlands : Imprint: Springer, 2016)
This textbook provides a comprehensive compilation of conceptual perspectives, methodological approaches and empirical insights of inter- and transdisciplinary sustainability science. Written by an international team of authors from leading sustainability institutions, the textbook covers key perspectives and topics of the scientific discourse on sustainable development. More than two decades after conceptualizing sustainability as societal guiding vision and regulative idea the necessity of concretizing and realizing sustainability in societal praxis is bigger than ever. Sharply improved individual and societal sustainable decision-making and action is necessary for a better future of humankind and the planet. On that account problem- and solution-oriented perspectives and competencies are crucial. The different chapters assemble an encompassing view of essential foundations and specific areas of research and action in sustainability science and practice. The textbook aims at fostering the further establishment of sustainability science in higher education and to enable the next generation of sustainability experts to tackle the challenging and exciting topic of sustainable development.